A Novel, Wide Angle, High Resolution Direction-Of-Arrival Detector - Vinci, Gabor; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (European Microwave Week (EuMW) 2011, 2011)
Direction-Of-Arrival (DOA) detection is a demanding task for a wide range of applications where high accuracy, robustness, small size, and low cost are important requirements. An innovative Six-Port based DOA detector is hereby presented. Several applications benefit from the advantages of this new interferometric detection principle. A new high resolution dual Six-Port based detector is presented featuring among the advantages provided by the interferometric principle also a wide angle of detection as well as an increased dynamic range and new digital signal processing strategies.
elib2cris::1512001600,vinci2011b
Keywords: Accuracy; Calibration; Detectors; Polynomials; Radio frequency; Receiving antennas